PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT ANDIARTA MUZIZAT KOTA TANGERANG - Rosita Marliana; Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the influence of the physical work environment and work motivation on employee performance at PT. Andiarta Muzizat, Tangerang City, both partially and simultaneously. A quantitative method was employed, with a population consisting of 70 respondents. Saturated sampling was used, resulting in a total sample size of 70 respondents. Data analysis included validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results show that the physical work environment (X1) significantly affects employee performance (Y), with the regression equation Y=14.523+0.655X_1. The hypothesis test yielded a calculated T-value greater than the table value (3.846 > 1.995), leading to the rejection of Ho1 and acceptance of Ha1. This indicates a significant effect of the physical work environment on employee performance. Similarly, work motivation (X2) significantly influences employee performance (Y), with a regression equation of Y=14.434+0.615X_2. The hypothesis test showed a calculated T-value exceeding the table value (3.098 > 1.995), resulting in the rejection of Ho2 and acceptance of Ha2, confirming a significant influence of work motivation on employee performance. Furthermore, the simultaneous effect of the physical work environment (X1) and work motivation (X2) on employee performance (Y) is significant, as shown by the regression equation Y=8.903+0.509X_1+0.307X_2. The hypothesis test indicated a calculated F-value higher than the table value (8.414 > 3.13), leading to the rejection of Ho3 and acceptance of Ha3. This means both variables simultaneously have a significant effect on employee performance.